The effect of starch isolation method on physical and functional properties of Portuguese nut starches. 2. Q. rotundifolia Lam. and Q. suber Lam. acorns starches - Correia, Paula Reis (2015)
A new starch was isolated from fruits of two acorn species, Quercus rotundifolia and Quercus suber by alkaline (A3S) and enzymatic (ENZ) methods and physical and functional properties were studied. The isolation method induced changes in most of those properties in the isolated starches, mainly in resistant starch content, syneresis, pasting, thermal and rheological properties. Isolated acorn starches presented high amylose content (53e59%) and resistant starch content (30.8e41.4%). Acorn starches showed limited and similar solubility values and swelling power values, showing a gradual increase from 60 C to 90 C. The pasting temperatures ranged from 67.5 to 72.0 C and pastes did not present breakdown, which is suggestive of a high paste stability of acorn starches during heating. At ambient temperature the turbidity and syneresis values were low, but when held at freezing temperatures the syneresis significantly increased. Thermal analysis revealed that the acorn starches easily undergo transition phenomena as shown by the low To and enthalpy values (4.1e4.3 J/g), these effects were more evident in starches isolated by ENZ method. Pastes are more elastic than viscous and form strong gels after cooling. Q. suber starch was shown to be more sensitive to the effect of isolation method. Generally, starch isolated by enzymatic method presented less interesting functional properties, since this isolation procedure greater affected the raw structure of starches